Flood Water Filtration and Purification System - Izzah Rufaidah Mohd Iqram; Izzah Husnina Kana’in; Noor Amirah Mohamad; Durratun Nasihin Muhammad Hadafi; Haslinawati Mohd Mustapha (Kolej PERMATA Insan, 2024)
4th Insan Junior Researchers International Conference 2023 (iJURECON 2023) : "STREAM for a better future”/ editors : Ahmad Fuad Mohamad Amin, Nurhidaya Mohamad Jan, Nur Aisyah Mohamed, Nur Fatin Fathillah Mazlan 27-28 October 2023 Organized by : Kolej Permata Insan